Mining and selecting genes encoding chitinase from DNA metagenome data - Thi Thom, Nguyen; Thi Hong Ha, Nguyen; Bich Ngoc, Pham; Hoang Ha, Chu; Bich Hai, Ho; Mai Huong, Le (Vietnam Journal of Biotechnology, 2020)
In this study, genes encoding chitinaseswere obtained by mining the rhizosphere metagenome database of 2-year-old replanted coffee trees in Dak Lak province and annotating using CAZy data. These sequences predictably are covered 90% of chitinase domains by BLASTp and range from 33% to 99% identity in comparison with published sequence data of chitinase genes. In order to find new funtional chitinase gene(s), among 8/56 chitinase genes with sequence identity less than 75%, ChiA_2 sequenceshowed the highest max score andsignificant homology (72%) was initially selected. Analysis of in silico sequence identified a protein motif for a signal peptide of 30 amino acid residues at the N- terminal using SignalP 4.1 server. By InterProscan software, the ChiA_2 gene sequence is predicted to have conserved active site FDGIDIDWE located at 134-142. The ChiA_2 sequence consisting of 1167 nucleotides, encoding for 389 amino acids with a predicted molecular mass of 43 kDa was synthesized, cloned into the pET21 a(+) vector and transformed into E. coli BL21 (DE3) by heat shock. ChiA_2 protein was specifically expressed in the recombinant E. coli BL21 (DE3) cell with an activity of 4.9 U/ml. In this study, analyzing metagenomic data from the soil sample of rhizosphere provided relatively sufficient genetic information of chitinase gene and initially successful expression and functional evaluation of ChiA_2 sequence, encoding Chitinase 2.